Female urethroplasty with a flap of the oral mucosa in a patient with in idiopathic urethral stricture. Clinical case - A. S. Al-Shukri; Ju. A. Ponomareva; A. V. Maksimova; N. I. Dub; A. A. Andriyanov; A. A. Manchenko; S. B. Petrov (Вестник хирургии имени И.И. Грекова)
This article presents a clinical case of a rare pathology in urological practice – idiopathic stricture of the female urethra, considers the tactics of patient management and the method of surgical correction.